2014
DOI: 10.1371/journal.pone.0093284
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Spinal Mechanisms of Task Failure of Sustained Submaximal Fatiguing Contractions

Abstract: In this and the subsequent companion paper, results are presented that collectively seek to delineate the contribution that supraspinal circuits have in determining the time to task failure (TTF) of sustained submaximal contractions. The purpose of this study was to compare adjustments in supraspinal and spinal excitability taken concurrently throughout the performance of two different fatigue tasks with identical mechanical demands but different TTF (i.e., force-matching and position-matching tasks). On separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 88 publications
3
21
2
Order By: Relevance
“…The decrease in SICI we observed during sustained fatiguing voluntary activity of the elbow flexor muscles is consistent with the reduction in intracortical inhibition (SICI) when tested after fatiguing exercise while the muscle was at rest (Benwell et al 2006; Maruyama et al 2006; Takahashi et al 2009; Vucic et al 2011), and the recent report of decreasing inhibition during sustained submaximal contractions with a constant target force and hence, increasing EMG (Williams et al 2014). Voluntary activity that is not fatiguing lessens SICI (Ridding et al 1995; Fisher et al 2002; Ortu et al 2008) but here SICI decreased from control contractions to the end of the fatiguing contraction with a constant EMG (Figure 2 shows an increase in values toward the unconditioned MEP, indicating less inhibition).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The decrease in SICI we observed during sustained fatiguing voluntary activity of the elbow flexor muscles is consistent with the reduction in intracortical inhibition (SICI) when tested after fatiguing exercise while the muscle was at rest (Benwell et al 2006; Maruyama et al 2006; Takahashi et al 2009; Vucic et al 2011), and the recent report of decreasing inhibition during sustained submaximal contractions with a constant target force and hence, increasing EMG (Williams et al 2014). Voluntary activity that is not fatiguing lessens SICI (Ridding et al 1995; Fisher et al 2002; Ortu et al 2008) but here SICI decreased from control contractions to the end of the fatiguing contraction with a constant EMG (Figure 2 shows an increase in values toward the unconditioned MEP, indicating less inhibition).…”
Section: Discussionsupporting
confidence: 88%
“…Others however, showed no significant changes in ICF of the exercised limb after fatigue (Maruyama et al 2006), although fatigue suppressed ICF in the homologous non-exercising muscle for up to 6 min after a fatiguing contraction of the first dorsal interosseous (FDI) (Baumer et al 2002). In addition, Williams et al (2014) found no change in ICF during a fatiguing submaximal contraction. However, facilitation prior to fatigue was minimal (conditioned MEP 104–107% of unconditioned).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…; Williams et al. ), our more extended (135‐degree) elbow joint provided a slightly different position. In addition to the obvious biomechanical changes, potential changes in the muscle activation patterns of the synergistic muscles (e.g., deltoid muscles, rotator cuffs) might also have occurred (Rudroff et al.…”
Section: Discussionmentioning
confidence: 73%